Interactivity and e-Learning - An experimental study - Roznawski, N.; Wiemeyer, J. (International Journal of Computer Science in Sport, 2010)
Interactive features play an important role in e-learning. In this paper we report an experimental pilot study which tested e-learning units with different degrees of interactivity. A specific experimental design adapted to a blended-learning scenario was developed. Participants learned with e-learning units, dealing with different movement analysis concepts (MACs), which differ only in interactive features (different degrees of interactivity). Pretest and posttest measured participants` basic knowledge and knowledge transfer of the MACs. A further measurement of participants` basic knowledge was performed immediately after learning. Moreover participants` experience of activation and interactivity was assessed by a questionnaire. The results show that students could improve their knowledge. However we did not find any significant impact of different degrees of interactivity. This result may be due to confounding problems or a small sample size. In some items the groups who learned interactively or actively rated activation and interactivity higher than the non-active or non-interactive groups. Open-ended questions showed, that when being exposed to non-interactive or non-active e-learning units students complained about the absence of interactive features.